Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/ico.0b013e318294f97e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rebamipide Ophthalmic Suspension on Optical Quality in the Short Break-up Time Type of Dry Eye

Abstract: Rebamipide administered to treat the short BUT type of dry eye significantly improved optical quality because of the improvement in tear stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…Koh et al60 reported finding significant increases in the tear film break-up time, and there were significant upward curves from the baseline in terms of the total corneal higher-order aberrations, coma-like aberrations, and spherical-like aberrations after the application of rebamipide (Figure 4). In addition, their study demonstrated that rebamipide improved tear stability, possibly leading to improved optical quality.…”
Section: Rebamipide For Clinical Applicationmentioning
confidence: 94%
See 1 more Smart Citation
“…Koh et al60 reported finding significant increases in the tear film break-up time, and there were significant upward curves from the baseline in terms of the total corneal higher-order aberrations, coma-like aberrations, and spherical-like aberrations after the application of rebamipide (Figure 4). In addition, their study demonstrated that rebamipide improved tear stability, possibly leading to improved optical quality.…”
Section: Rebamipide For Clinical Applicationmentioning
confidence: 94%
“…Promotional and commercial use of the material in print, digital or mobile device format is prohibited without the permission from the publisher Lippincott Williams & Wilkins. Please contact journalpermissions@lww.com for further information 60. Copyright © 2013.…”
Section: Figurementioning
confidence: 99%
“…Administration of topical rebamipide increases secretion of mucins from goblet cells and improves the ocular surface in short break-up time type of dry eye 1,2. The human eyelid margin looks histologically to be an important structure for the maintenance of tear film 3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the clinical effects of rebamipide eye drops (Mucosta® ophthalmic suspen sion UD2%; Otsuka Pharmaceutical Co, Ltd, Tokyo, Japan) for various types of dry eye were reported 1,2,23,24. Rebamipide eye drops for dry eye are also being developed for approval in the US.…”
Section: Introductionmentioning
confidence: 99%
“…32 A series prospective studies have demonstrated that rebamipide suspension has significant effect of improving fluorescein corneal staining, lissamine green conjunctival staining, Schirmer's test, tear-film breakup time, and dry eye-related ocular symptoms without serious adverse reaction. 31,[33][34][35] Meanwhile, there is increasing evidence that the excessive expression of inflammatory mediators, such as IL-8, IL-6, IL-1β, and TNF-α, on the ocular surface may have an important role in DES pathogenesis and clinical symptoms. [36][37][38] These cytokines promote the activation and migration of leukocytes, the expansion of pathogenic T cells and the production of other proinflammatory factors that mediate DES.…”
Section: Discussionmentioning
confidence: 99%